Dampak pengumuman Covid-19 terhadap harga dan volume saham pada industri farmasi di Indonesia - Pujo Gunarso; Jason Nathaniel; Ani Rustia Dewi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
The purpose of this study is to analyze the effect of the announcement of Covid-19 in Indonesia on stock prices and the volume of shares traded by the pharmaceutical industry listed on the Indonesia Stock Exchange in 2020. Research on the pharmaceutical industry with a sample of 10 companies. The research period is 360 days or 180 days before and after the announcement of Covid-19. The event study methodology analyzes the market reaction to an event, namely the announcement of the Covid-19 pandemic and data analysis techniques using the Wilcoxon Sign Rank Test. The results of the study explain that there are insignificant differences in share prices and significant differences in the volume of shares traded, which means that the announcement of Covid-19 has information content as indicated by an increase in the volume of shares traded.